AN ANALYSIS OF TEACHERS’ LANGUAGE POLITENESS DURING TEACHING ENGLISH - Sumbayak, Lasni; Nasution, Jamaluddin (Jurnal Bahasa Indonesia Prima (BIP), 2022)
The objective of the study was to express language politeness in teacher-student conversations to the way educating and learning at SMP Negeri 21 Medan. This study makes use of qualitative method. The techniques used in data collection are observation, transcription techniques, and take notes techniques. The target is to find out the use of language politeness principles in learning activities on the choice of words and polite ways of speaking between teachers and students. The outcomes of this study show that use of politeness in language is influenced by teacher’s emotions and there are seven maxims out of ten maxims use used by teacher’s in language politeness namely 1) opinion reticente maxim, 2) agreement maxim, 3) sympathy maxim, 4)generosity maxim, 5) approbation maxim, 6) obligation of S to O Maxim, 7) Tact maxim. In conclusion, the politeness of communication between teacher’s and students tends to use Indonesian rather than English. This is a concern for teachers in teaching in class by speaking polite language.